Feeders and rations forms for swine, upon ration losses - Bellaver, Cláudio; Konzen, Egidio A.; Santos, Dalton L.; Freitas, Alfredo R. (Pesquisa Agropecuaria Brasileira, 2014)
This experiment was carried out with the objective of comparing EMBRAPA’s prototype feeders (C1) and conventional feeders (C2), as well as two physical forms of rations, pelleted (R1) and meal (R2). The experimental design was the entirely randomized, with factorial structure 2 x 2 and with the experimental unit represented by the ration losses/pen/day. The utilized animals weighted 77.48 ± 0.48 kg, and the pens were of entirely stripped floor. An interaction statistically significant (P<0.01) was found among feeders and rations. Between C1 and C2 , R2 showed significantly (P<0.01) higher ration losses than R1 although proportionaly smaller for C2. The percentual loss of rations was 1.37 ± 0.58 and 0.99 ±0.22 for feeders C1 and C2, respectively.